2016
DOI: 10.1007/s11883-016-0580-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Atherosclerosis: Recent Data and Future Directions

Abstract: Historically the relationship between exercise and the cardiovascular system was viewed as unidirectional, with disease resulting in exercise limitation and hazard. This article reviews and explores the bidirectional nature, delineating the effects, generally positive, on the cardiovascular system and atherosclerosis. Exercise augments eNOS, affects redox potential, and favorably affects mediators of atherosclerosis including lipids, glucose homeostasis, and inflammation. There are direct effects on the vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
0
10
0
1
Order By: Relevance
“…So being physically active reduces the risks for obesityrelated cardiovascular disease by positively influencing autonomic nerve function [2,16,36] and insulin resistance [37], besides reducing the action of catecholamines (attenuating acetylcholine-oriented vasoconstriction), which reduce resting HR, and during submaximal exercise, allowing for faster HR recovery, which indicates improved vagal modulation and less risk for cardiovascular outcome [38,39]. In this scenario, healthy lifestyle was associated with higher HRV, suggesting a positive effect on ANS and throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…So being physically active reduces the risks for obesityrelated cardiovascular disease by positively influencing autonomic nerve function [2,16,36] and insulin resistance [37], besides reducing the action of catecholamines (attenuating acetylcholine-oriented vasoconstriction), which reduce resting HR, and during submaximal exercise, allowing for faster HR recovery, which indicates improved vagal modulation and less risk for cardiovascular outcome [38,39]. In this scenario, healthy lifestyle was associated with higher HRV, suggesting a positive effect on ANS and throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…Complex factors, such as shear stress and alternations in plasma profiles precipitate the activation or restoration of endothelial pathways during exercise [51]. Exercise-induced circulating catecholamines could act on β-3 adrenergic receptors (B3AR) to increase endothelial nitric oxide synthase (eNOS), which augments the bioavailability of NO (nitric oxide), an essential molecule responsible for vasodilation and anti-atherosclerosis effects [52,53,54,55]. More recent evidence suggested that rhythmic handgrip exercise promoted increased eNOS phosphorylation, NO generation, and O 2 − production, along with improved autophagy markers including Beclin1, microtubule-associated proteins 1A/1B light chain 3B (LC3B), autophagy-related gene 3 (Atg3), and lysosomal-associated membrane protein 2A (LAMP2) as well as decreased levels of p62 in endothelial cells from human radial artery [56].…”
Section: Contemporary Theory Behind Exercise-induced Cardiovasculamentioning
confidence: 99%
“…[79] Additionally, many molecules like Beclin1 and Autophagy-Related Gene 3 (Atg3) increases versus reduction in p62 a classical receptor for autophagy, which boosted autophagy regulation on vessel's endothelium. [80][81][82]…”
Section: Endothelial Effectmentioning
confidence: 99%